A new species of the catfish Neoplecostomus (Loricariidae: Neoplecostominae) from a coastal drainage in Southeastern Brazil - Cherobim, Arieli Matheus [UNESP]; Lazzarotto, Henrique; Langeani, Francisco [UNESP] (FapUNIFESP (SciELO), 2016)
A new species of loricariid catfish is described from the rio Perequê-Açú and surrounding basins, Parati, Rio de Janeiro State. The new species has the accessory process of ceratobranchial 1 more slender than the main body of the ceratobranchial, and a very large sesamoid ossification, markedly greater in size than the interhyal. Additionally, the new species presents a distinct dorsal color pattern consisting of a conspicuous horseshoe shaped light blotch with a central dark area posterior to the supraoccipital.
Keywords: Cascudos; Neoplecostomus microps; Perequê-Açú; Siluriformes; Taxonomy